EDUCATION WITH AUDIOVISUAL MEDIA ON ATTITUDES AND BEHAVIOR OF HALAL FOOD CONSUMPTION IN HIGH SCHOOL STUDENTS - Permana, Endah Budi; Mardhotillah, Rachma Rizqina; karya, denis (Jurnal Bisnis dan Keuangan, 2022)
Islam requires its followers to consume halal food. The rapid development of the media causes the flow of information to be obtained more easily and a lot so that it can affect a person's consumption pattern. Factors that can influence a person's decision to consume halal food are attitudes and behavior. Audiovisual media are considered better and more interesting in displaying information so that understanding is obtained, and a good attitude can also change a person's behavior.  The purpose of the study was to analyze differences in attitudes and behavior before and after being given education with audiovisual media in high school students. The type of research used is an experimental design with a two-group design with pre-test and post-test. The study was conducted on students of SMA Hang Tuah 2 Sidoarjo. The sample required is 86 people who are divided into 2 groups, namely 42 students in the poster and discussion group (P1) and 42 students in the video group (P2), with a sampling technique that is cluster sampling. The data collection instrument used was a questionnaire of respondents' attitudes and behavior in consuming halal food. The results are there is a significant difference between the attitude of consuming halal food in the group that was given education with video media (p-value 0.000) compared to posters and discussions (p-value 0.249). There is also a significant difference between the consumption behavior of halal food in the group that was educated with video media (p-value 0.000) compared to posters and discussions (p-value 0.119). The conclusion of this study, halal food education will be effective in changing attitudes and behavior in high school students if it is given with audiovisual media in the form of the video so that this educational strategy can be applied to other target groups such as university students.